PENGARUH PENERAPAN STRATEGI SQ4R TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS V SD NEGERI 020 RAMBAH HILIR - Anggi Elpina; Otang Kurniaman, Erlisnawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to investigate the effect of the SQ4R strategy during the 2023/2025 academic year. The type of research employed is a non-equivalent control group design involving two classes, namely the experimental class and the control class. The subjects of this study were Class VB as the control group, consisting of 21 students, and Class VA as the experimental group, also consisting of 21 students. The researcher implemented the SQ4R strategy in the experimental class, while conventional teaching methods were applied in the control class. Students' reading comprehension skills were measured using a test based on reading materials. The results of the study showed that the hypothesis tested using the t-test yielded a significance value of 0.024 < 0.05, indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. These findings suggest that the SQ4R strategy has a significant effect on students' reading comprehension skills.